1994
DOI: 10.1007/bf02059596
|View full text |Cite
|
Sign up to set email alerts
|

Toward the chemical ecology of medicinal plant use in chimpanzees: The case ofVernonia amygdalina, a plant used by wild chimpanzees possibly for parasite-related diseases

Abstract: The bitter and related constituents have been isolated fromVernonia amygdalina (Compositae), a plant ingested by wild chimpanzees possibly suffering from parasite-related diseases in the Mahale Mountains National Park, Tanzania. Isolated from the plant were four known sesquiterpene lactones, seven new steroid glucosides, and two aglycones of the glucosides. The sesquiterpene lactones showed significant in vitro antischistosomal, plasmodicidal, and leishmanicidal activities. Antischistosomal activity was also f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 100 publications
(57 citation statements)
references
References 15 publications
3
51
0
1
Order By: Relevance
“…The test was assayed using the method reported previously by Ohigashi et al (1994). Briefly, adult pair of schistosomes of Egyptian strain S. mansoni was cultured in RPMI-1640 medium.…”
Section: In Vitro Anti-schistosomal Activitymentioning
confidence: 99%
“…The test was assayed using the method reported previously by Ohigashi et al (1994). Briefly, adult pair of schistosomes of Egyptian strain S. mansoni was cultured in RPMI-1640 medium.…”
Section: In Vitro Anti-schistosomal Activitymentioning
confidence: 99%
“…Parasite loads decrease dramatically after animals consume that plant, and overt signs of disease disappear (Huffman and Seifu, 1989;Huffman et al, 1993). V. amygdalina contains sesquiterpene lactones and steroid glucosides with antiparasitic activity at the doses consumed by the animals Ohigashi et al, 1994). PSMs in V. amygdalina also have been effective at controlling nematodes that cause significant losses of livestock in the tropics (Plotkin, 2000).…”
Section: Self-medicationmentioning
confidence: 99%
“…Behavioral, ecological, and pharmacological studies have shown that the great ape diet contains a variety of plant parts of no apparent nutritional significance, which may be consumed because of their secondary compounds [e.g., Huffman et al, 1998a;Jisaka et al, 1992;Koshimizu et al, 1993;Wrangham & Waterman, 1983;Wrangham et al, 1998]. It has been suggested that some of these dietary plants may also have medicinal properties [Huffman, 2003;Huffman et al, 1998a,b;Ohigashi et al, 1994]. Chemical investigations of the medicinal hypothesis have focused mainly on the consequences of two types of non-nutritional ingestion (i.e., ingestion of items that appear to be of little or no nutritive significance) in chimpanzees: 1) swallowing whole leaves of various species, and 2) ingesting the bitter pith of Vernonia amygdalina [Huffman & Seifu, 1989;Wrangham & Goodall, 1989;Wrangham & Nishida, 1983].…”
Section: Introductionmentioning
confidence: 97%
“…Messner and Wrangham [1996] examined the in vitro anthelmintic activity of Rubia cordifolia rough leaves, but no significant activity was observed. On the other hand, bitter pith has been shown to have potential pharmacological consequences because it contains chemical compounds that apparently are responsible for the control of nematode infections [Huffman et al, , 1996aKoshimizu et al, 1993;Ohigashi et al, 1994]. Furthermore, it has been suggested that compounds found in the ordinary diet of animals may have important positive effects on health and may prevent risks of infection and illness [Huffman, 1997;Huffman et al, 1998a;Janzen, 1978].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation